(untitled) (Bangladesh Journal of Nuclear Medicine, 2019)
In nuclear medicine practices, internal radiation dosimetry offers methods for calculation of radiation absorbed dose and risks from radionuclides incorporated inside the body. To manually perform internal radiation dosimetry is time-consuming and errors can occur in each step leading to developing software tools to ease users. There are many software packages available; however, many of them have limited functions. Locally developed IRDE software has been used to calculate the absorbed dose per unit of radioactivity in the target organ. The dose calculation methodology in nuclear medicine practices is described in this study along with a preliminary result on dose calculation for Bangladeshi population due to ingestion of 131I radioisotope in nuclear medicine practices. IRDE is user-friendly, graphic user interface-based software. It can be performed all steps of internal dosimetry within single environment lead to reducing calculation time and reducing possibility of error. IRDE also provides fast and accurate results which may be useful for a routine work in nuclear medicine facilities. Bangladesh J. Nuclear Med. 21(1): 26-30, January 2018